Insight into mechanics of externally indeterminate hardwood–concrete composite beams. (15th January 2016) - Sebastian, W.M.; Mudie, J.; Cox, G.; Piazza, M.; Tomasi, R.; Giongo, I.
Highlights: Tests on externally indeterminate hardwood LVL–concrete composite beams. Use of a special test to assess connection behaviour in cracked concrete. Comparing behaviours using fully or partially threaded screw connectors. Checks on internal consistency of slip, strain, deflection and load data sets. Abstract: This paper presents tests on beech LVL–concrete slab composite connections and externally indeterminate beams using connectors comprising fully threaded (FT), small-headed screws or partially threaded (PT), large-headed screws in X-formation. A test was devised to quantify connection characteristics in fully cracked concrete (applicable to hog zones of the beams). Relative to the FT-based connections, the PT-based connections were of greater strength, nonlinearity and flexibility in compression concrete, and weaker, less stiff but more ductile in tension concrete. One composite beam exhibited 22% redistribution of support reaction at 88% of the failure load. Failure occurred primarily at the connections, which then gradually led to fracture of the LVL as a secondary mode of failure.